저변동성 이상현상과 투자전략의 수익성 검증 - 고봉찬(Bong Chan Kho); 김진우(Jin Woo Kim) (한국증권학회지, 2014)
본 연구는 한국거래소(KRX) 유가증권시장에 상장된 주식들을 대상으로 고변동성 주식이 저변동성주식에 비해 낮은 성과를 보이는 저변동성 이상현상이 존재하는가를 검증하고, 이에 기반하는 투자전략이 유효한 초과수익성을 보이는지, 그리고 그 특성과 원인은 무엇인지를 검증하였다. 1990년 1월부터 2012년 12월까지 매월 과거 주식수익률의 고유변동성에 따라 5개 포트폴리오를 재구성해 나가면서, 고유변동성이 가장 낮은 포트폴리오(P1)를 계속 매수보유하는 경우 전체기간에서 거래비용 차감 후 218%의 보유수익을 얻는 반면, 고유변동성이 가장 높은 포트폴리오(P5)는 -98%의 보유손실을 입는 것으로 나타났다. 이는 고변동성 포트폴리오에 장기투자하는 것은매우 열등한 투자성과를 가져오게 됨을 의미한다. 또한, 매월 P1을 매수하고 P5를 매도하는 헤지펀드 투자전략(P1-P5)은 전체 기간에서 거래비용 차감 후 월평균 1.57%의 유의한 초과수익률을얻는 것으로 나타나서 국내 주식시장에서도 저변동성 이상현상이 유의하게 존재하고 이에 기반하는투자전략이 유효한 것으로 분석되었다. 특히 이러한 투자전략의 수익성은 2000년 이후 기간에서만유의하게 나타나며, 1,000원 미만의 저가주와 거래회전율 하위 10%의 비유동성 주식을 제거한표본에서도 월평균 1.82%의 유의한 초과수익률을 보였으며, 거래비용 절감을 위해 포트폴리오재구성 주기를 월간에서 분기나 반기로 늘리거나 보유기간을 월간에서 3년까지 늘리더라도 초과수익률이 지속적으로 발생하는 것으로 나타났다. 이러한 결과가 발생되는 원인을 파악하기 위하여 변동성 포트폴리오 구성주식들의 수익률 특성을분석한 결과, 고변동성 주식들 중에서 거래회전율이 높고 과거 수익률의 왜도가 높은 주식일수록과대평가 오류가 발생하여 사후 수익률이 저변동성 주식들보다 낮게 나타나는 것으로 분석되었다. 특히 이러한 변동성에 따른 수익률 격차는 기대왜도가 높은 그룹에서만 유의하게 발견됨으로써,고변동성뿐만 아니라 고왜도를 갖는 복권적 주식에 대한 노이즈 투자자들의 선호에 기인하는 과대평가 오류가 사후적으로 조정되면서 저변동성 이상현상이 발생하는 것임을 시사하고 있다. The low volatility anomaly is a phenomenon recently observed in many countries, wherehigh volatility stocks underperform low volatility stocks in subsequent periods. In this paper,we examine whether such low volatility anomaly is found in Korean stock markets and whatare the characteristics and causes of the anomaly. Using the KOSPI-listed stocks with at least 12 monthly returns from January 1990 to December2012, we show that the low volatility anomaly is found significantly in Korean stock market. Specifically, among quintile portfolios constructed each month based on idiosyncratic volatilityof past stock returns, the buy-and-hold returns of the lowest volatility portfolio (P1) over thesample period amount to 218% after transaction costs, whereas those of the highest volatilityportfolio (P5) reach -98%. The hedge portfolio of buying P1 and selling P5 each month earnssignificantly positive return of 1.57% per month on average after transaction costs. Especially,this low volatility anomaly is significant only for the period after 2000. In addition, regardlessof the portfolio rebalancing period used and the holding period used, the hedge portfolio earnssignificantly positive excess returns consistently. From regression analyses to analyze the characteristics and causes of this anomaly, we findthe underperformance of high volatility stocks is concentrated in stocks with high turnover andhigh skewness in their idiosyncratic returns. This implies that the anomaly could be related tothe presence of noise traders who prefer lottery-like stocks with high volatility and highskewness, inducing an overvaluation bias that is corrected in subsequent periods to a fundamentalvalue. In order to test this hypothesis, we estimate the expected skewness of idiosyncraticreturns and find that the low volatility anomaly is found significantly only for stockswith high volatility and high expected skewness. This supports the hypothesis that the presenceof noise traders preferring lottery-like stocks results in the low volatility anomaly in Koreanstock market. KCI Citation Count: 27